النماذج التطبيقية في مكافحة الفقر في الإسلام - عون الله يمينة; مروة خزان (university of eloued جامعة الوادي, 2025)
لا تزال ظاهرة الفقر مثار جدلا واسع في الوسط الأكاديمي والسياسي. يمتد هذا الخلاف من مفهوم الفقر وأسبابه إلى طرق تحجيمه. يبرز هذا الاختلاف بشكل خاص بين الفكر الاسلامي والفكر الوضعي. تهدف هاته المذكرة إلى دراسة ظاهرة الفقر من منظور إسلامي شامل، من خلال تحليل المفاهيم الأساسية المرتبطة به واستعراض الأدوات الشرعية المعتمدة لمكافحته مثل الزكاة والوقف والصدقات والقرض الحسن. نعتمد في هاته المذكرة بالأساس على المنهج التاريخي من خلال عرض النماذج التأسيسية في العصر النبوي والخلافة الراشدة، ثم تقديم تطبيقات متنوعة في العصور الإسلامية اللاحقة، بما في ذلك الأموية والعباسية والعصور المتأخرة؛ كما استعرضت المذكرة الجهود الحديثة في بعض الدول الإسلامية من خلال تجارب مؤسسات الزكاة، وصيغ الوقف المعاصر، وبرامج التمويل الإسلامي المصغر. أكدت المذكرة على أن المنظومة الإسلامية بمنهجها المتكامل الذي يراعي الأبعاد الروحية والاقتصادية والاجتماعية تقدم نموذجًا فعالا في مكافحة الفقر، ويمكن الاستفادة منه في السياسات الحديثة المعنية بالتنمية والعدالة الاجتماعية The phenomenon of poverty remains a subject of extensive debate within academic and political spheres. This disagreement spans from the very concept and causes of poverty to the methods for its alleviation. The divergence is particularly pronounced between Islamic and secular thought. This thesis aims to study the phenomenon of poverty from a comprehensive Islamic perspective by analyzing its fundamental concepts and examining the Shari'ah-based instruments for combating it, such as Zakat (obligatory alms), Waqf (endowment), Sadaqat (voluntary charity), and Qard al-Hasan (benevolent loans). The thesis primarily employs a historical methodology, presenting the foundational models from the Prophetic era and the Rightly-Guided Caliphate, followed by diverse applications in subsequent Islamic periods, including the Umayyad, Abbasid, and later eras. Furthermore, the study examines modern efforts in several Muslim countries through the experiences of Zakat institutions, contemporary forms of Waqf, and Islamic microfinance programs. The thesis concludes that the Islamic framework, with its integrated approach that considers the spiritual, economic, and social dimensions, offers an effective model for poverty alleviation. It argues that this model can be drawn upon to inform modern policies concerned with development and social justice.
ماستر
Keywords: فقر زكاة وقف صدقات الخلافة الراشدة قرض حسن الدولة العباسية الدولة الأموية poverty zakat Wakf Sadaqah Qard-Al-Hassan